2021
DOI: 10.1073/pnas.2022590118
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide role of codon usage on transcription and identification of potential regulators

Abstract: Codon usage bias is a fundamental feature of all genomes and plays an important role in determining gene expression levels. The codon usage was thought to influence gene expression mainly due to its impact on translation. Recently, however, codon usage was shown to affect transcription of fungal and mammalian genes, indicating the existence of a gene regulatory phenomenon with unknown mechanism. In Neurospora, codon usage biases strongly correlate with mRNA levels genome-wide, and here we show that the correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 49 publications
(67 reference statements)
0
29
1
Order By: Relevance
“…Our observed tissue-specific protein expression of rare codon-enriched reporters in the testis and brain could be primarily driven at the protein level, but could also be regulated at the level of mRNA (reviewed in Radhakrishnan & Green, 2016). Rare codons can decrease levels of transcription (Zhao et al, 2021; Z. Zhou et al, 2016) or can negatively impact mRNA stability through a growing number of characterized mechanisms and in numerous model systems (Bazzini et al, 2016; Burow et al, 2018; Buschauer et al, 2020; Presnyak et al, 2015; Radhakrishnan et al, 2016; Wu et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Our observed tissue-specific protein expression of rare codon-enriched reporters in the testis and brain could be primarily driven at the protein level, but could also be regulated at the level of mRNA (reviewed in Radhakrishnan & Green, 2016). Rare codons can decrease levels of transcription (Zhao et al, 2021; Z. Zhou et al, 2016) or can negatively impact mRNA stability through a growing number of characterized mechanisms and in numerous model systems (Bazzini et al, 2016; Burow et al, 2018; Buschauer et al, 2020; Presnyak et al, 2015; Radhakrishnan et al, 2016; Wu et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Use of preferred codons speeds up the local rate of translation elongation while rare codons slow down translation elongation and potentially result in ribosome pausing and premature termination, a mechanism that can affect translation efficiency ( 21 , 23 ). We also showed that codon usage could influence gene expression levels by affecting transcription efficiency ( 13 , 33 , 64 ). These results led us to propose that codon usage represents a code within the genetic codons that regulates both gene expression level and protein structure.…”
Section: Introductionmentioning
confidence: 87%
“…Actually, the advantage of transcriptional related genes and the actual abundance of nosZ transcript also provide the evidences for supporting the above speculation. Additionally, the prediction of nos genes expression by CAI values [47] further indicated that DM15 possessed the stronger expressed potential than DM22. Thus, the existence of dnr gene in the nos cluster of DM15 would be strongly linked to the stronger N2O reducing abilities in comparison with DM22.…”
Section: Discussionmentioning
confidence: 97%